Percutaneous treatment of severe retroperitoneal hematoma after percutaneous coronary intervention - Kumar, Agarwal Rajendra; Rajiv, Agarwal (Journal of Cardiology and Cardiovascular Medicine, 2021)
We describe a patient who developed severe retroperitoneal and intraperitoneal bleeding complicating femoral arterial catheterization for Percutaneous coronary intervention. Balloon tamponade of the actively bleeding femoral artery was effective in sealing off the leakage. This management strategy for this problem emphasizing an anatomical based interventional approach if the patient does not stabilize with volume resuscitation.